Evaluation of the Reflux Symptom Index and the Endolaryngeal Findings Scale after Treatment in Individuals with Laryngopharyngeal Reflux - Silva, Álvaro Siqueira; Duprat, André Campos; Machado, Súnia Ribeiro; Melo, Daniele Nahmias; Nascimento Ribeiro, Dayse Kelle (International Archives of Otorhinolaryngology, 2020)
Introduction Laryngopharyngeal reflux (LPR) is a prevalent condition in outpatients visiting the otorhinolaryngological clinic, with many controversies regarding its diagnosis and follow-up. Therefore, there is a need for clinical instruments that can diagnose individuals and monitor the results of their treatment.Objective To evaluate the applicability of the scores translated and adapted to Brazilian Portuguese: Reflux Symptom Index (RSI) and Endolaryngeal Reflux Findings Scale (ERFS), as instruments for post-treatment follow-up of LPR.Method A total of 35 individuals with atypical symptoms of gastroesophageal reflux disease and with an objective diagnosis of LPR, confirmed by high digestive endoscopy and 24-hour esophageal pH-metry dual probe test were submitted to the RSI and ERFS questionnaires, used in the pre- and post-treatment of 90 days with a Proton Pump Inhibitor.Result The evaluation of RSI and ERFS in the pre- and post-treatment showed a reduction in the results of the two scores, with a higher drop in the RSI (p < 0.001) than in the ERFS (p = 0.014). Although there was an improvement in the values in 23.9% of the individuals in the ERFS, there was no change in the category (p = 0.057), different from the RSI (p < 0.001), where there was a 67.4% improvement in values, as well as change in category (score went from positive to negative). There was a correlation between RSI and ERFS, moderate in the pretreatment and strong in the post-treatment.Conclusion The RSI and ERFS scores, when translated and adapted for Brazilian Portuguese and applied simultaneously, can be considered a good tool for post-treatment LPR follow-up.
Keywords: laryngopharyngeal reflux; proton pump inhibitors; treatment outcome